Tourism Village Management Based On Information Technology With Destination Management System - Singgih Purnomo; Endang Siti Rahayu; Asri Laksmi Riani; Suminah (LPPM Universitas Duta Bangsa Surakarta, 2019)
The development of technology has increased the ability of the tourism industry to increasingly develop. This is marked by the use of information and communication technology in tourism marketing. This study aims to review the implementation of the Destination Management System in Tourism Villages in Indonesia. This study uses qualitative methods and the object of this study is the Ponggok tourism village in Klaten Regency. The results show that the application of the Destination Management System in the tourism village is not optimal. The information and communication technology used is limited to social media, the web system owned by the village has not been optimized for online services.